DINAMIKA DAN TANTANGAN PERUBAHAN PENGGUNAAN LAHAN DI WILAYAH PULAU KECIL (STUDI KASUS GILI MENO, TRAWANGAN DAN AIR) - Selvia, Siska Ita; Iemaaniah, Zuhdiyah Matienatul (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
Gili Matra is a small island in the northern part of Lombok Island that is vulnerable to climate change's impacts. Rising sea levels, coastline changes, abrasion, rising earth temperatures, and global warming consequences cause climate change. The pressure on the need for space to develop facilities and infrastructure to support tourism has resulted in a change in land use from green open land to built-up land. Based on these problems, this research aims to describe the dynamics and challenges in regulating land use in Gili Matra. The method used in this research is a descriptive, evaluative analysis using policy analysis and DPSIR (Drivers, Pressures, States, Impacts, Responses) analysis to facilitate systematic thinking in analyzing research objectives. The results of this study indicate that tourism development is a trigger for the development of space requirements in Gili Matra, which causes changes in land use. In addition, there needs to be more overlap in determining area functions and spatial planning, resulting in stronger implementation of spatial use control in Small Islands.